2001
DOI: 10.1080/00288330.2001.9516976
|View full text |Cite
|
Sign up to set email alerts
|

Distributional expansion ofCarpophyllum flexuosumonto wave‐exposed reefs in north‐eastern New Zealand

Abstract: The native fucalean macroalga Carpophyllum flexuosum (Esper) Grev. has recently occupied many reefs on wave-exposed coasts in north-eastern New Zealand. At recently colonised sites, C. flexuosum occurs mainly on coralline-dominated areas with moderate densities of sea urchins (Evechinus chloroticus). At these sites, stipes of C. flexuosum are shorter, with more branching, reduced laminae, and increased stipe weights compared to those at sheltered sites. Survivorship of tagged individuals was less on wave-expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…Third, these changes occurred during a prolonged period of lower than average SSTs during an El Niño event. A similar pattern was found in other New Zealand seaweeds with Cole et al (2001) describing a correlation between the establishment of Carpophyllumflexuosum and decadal scale decreases in wave energy.…”
Section: Discussionsupporting
confidence: 53%
“…Third, these changes occurred during a prolonged period of lower than average SSTs during an El Niño event. A similar pattern was found in other New Zealand seaweeds with Cole et al (2001) describing a correlation between the establishment of Carpophyllumflexuosum and decadal scale decreases in wave energy.…”
Section: Discussionsupporting
confidence: 53%
“…It may, therefore, underestimate an observer's ability to categorise habitats. For example, the grouping of some urchin barrens quadrats in the C. flexuosum forest group is probably because of the occurrence of small, exposed growth forms of C. flexuosum in the urchin barrens habitat at some sites (Cole et al 2001). This also explains the separation of urchin barrens into two groups, one being urchin barrens with C. flexuosum present, the other being those without it (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have found that algae in more wave-exposed areas tend to be shorter with narrower and thicker lamina and stipes and fewer or no vesicles (Johnson and Koehl 1994, Kawamata 2001, Stewart and Carpenter 2003, Fowler-Walker et al 2006. These patterns have also been detected in Carpophyllum flexulosum (Esper) Greville (Cole et al 2001). Some of these patterns were found in C. maschalocarpum; individuals were shorter, and a lower proportion had vesicles in the more wave-exposed zones.…”
Section: Discussionmentioning
confidence: 77%